The potential of medicinal plants from heath forest: Local knowledge from Kelubi Village, Belitung Island, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Oktavia D, Pratiwi SD, Munawaroh S, Hikmat A, Hilwan I. 2022. The potential of medicinal plants from heath forest: Local knowledge from Kelubi Village, Belitung Island, Indonesia. Biodiversitas 23: 3553-3560. The heath forest ecosystem is home to hundreds of species in Belitung Island and is home to medicinal plant resources. The Belitung people prefer to use medicinal plants due to their easy availability and cheap therapy, compared to costly modern pharmaceuticals. In this study, we investigated the potential of medicinal plants from heath forests according to the local knowledge of the Belitung Malay community. This study was conducted in Kelubi Village, Belitung Island, Indonesia. Data and information related to medicinal plant properties were obtained through interviews with local people using an in-depth interview technique. We documented 86 species belonging to 48 families. The medicinal plants are classified into 48 families. The most abundant families are Rubiaceae (8 species), and Myrtaceae (8 species). Many species from the Myrtaceae family are used as medicinal species, such as, jemang (Rhodamnia cinerea), gelam (Melaleuca leucadendra), keremuntingan (Rhodomyrtus tomentosa), and sekudong pelandok (Syzygium buxifolium). The percentages of medicinal plant diversity based on habitus were 45% trees, 21% woody lianas, 13% small trees, 13% herbs, and 8% lianas. We also found that 23 species of medicinal plants were used as herbs after childbirth, and 10 species of plants were used to treat fever. Belitung Malay people use plants for traditional medicine to solve some diseases and therapy. We suggest that conservation efforts for the heath forest ecosystem should be a priority for the sustainable use of medicinal plants on Belitung Island.